Implementation of Design Thinking to Support Creativity-Oriented Learning: A Literature Review - Dina Syaflita; Ridwan Efendi; Muslim; Azhar (Jurnal Penelitian Pendidikan IPA, 2024)
Learning to Support the Implementation of Concepts for Real-World Problem Solving can be achieved by applying outcome-oriented learning that produces products as problem-solving solutions. Design Thinking is a strategy that can be utilized to support the achievement of these goals. This research aims to specifically examine the stages and characteristics of design thinking as a learning strategy oriented towards enhancing creativity. This research is a literature review study conducted using the narrative review method. The source of information used is secondary data in the form of literature related to design thinking in international journals. The literature selected is deemed capable of addressing the research questions. The results of this study indicate that design thinking is a learning process that can foster creativity. Design thinking involves a divergent thinking process in the problem-finding stage (empathy and design) and ideation. Creativity in both problem-finding and ideation resides in the realm of creative thinking. Problem-finding refers to the process of discovering various ways to obtain information about users. Ideation refers to the process of generating various solutions to solve user problems. Various literature studies demonstrate the role of design thinking in generating creative ideas and products to solve problems.